1994
DOI: 10.1121/1.408676
|View full text |Cite
|
Sign up to set email alerts
|

A computer model of amplitude-modulation sensitivity of single units in the inferior colliculus

Abstract: A computer model is presented of a neural circuit that replicates amplitude-modulation (AM) sensitivity of cells in the central nucleus of the inferior colliculus (ICC). The ICC cell is modeled as a point neuron whose input consists of spike trains from a number of simulated ventral cochlear nucleus (VCN) chopper cells. Input to the VCN chopper cells is provided by simulated spike trains from a model of the auditory periphery [Hewitt et al., J. Acoust. Soc. Am. 91, 2096-2109 (1992)]. The performance of the mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
75
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(76 citation statements)
references
References 41 publications
1
75
0
Order By: Relevance
“…An approach that has been taken to calibrate the neural tMTFs to different BMFs was the adjustment of membrane and potassium conductance time constants (Hewitt and Meddis, 1994;Guérin et al, 2006). For example, using membrane time constants in the order of 1 ms and conductance time constants in the 0.1-10 ms range for point neuron models of VCN chopper neurons, results in BMFs in the 40-400 Hz range (Hewitt and Meddis, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An approach that has been taken to calibrate the neural tMTFs to different BMFs was the adjustment of membrane and potassium conductance time constants (Hewitt and Meddis, 1994;Guérin et al, 2006). For example, using membrane time constants in the order of 1 ms and conductance time constants in the 0.1-10 ms range for point neuron models of VCN chopper neurons, results in BMFs in the 40-400 Hz range (Hewitt and Meddis, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…An approach that has been taken to calibrate the neural tMTFs to different BMFs was the adjustment of membrane and potassium conductance time constants (Hewitt and Meddis, 1994;Guérin et al, 2006). For example, using membrane time constants in the order of 1 ms and conductance time constants in the 0.1-10 ms range for point neuron models of VCN chopper neurons, results in BMFs in the 40-400 Hz range (Hewitt and Meddis, 1994). Besides the fact that tuning neuronal BMFs through ad-hoc calibration of conductance time constants can be regarded as a biologically Demanding assumption (specially when one considers the lack of calibration freedom that these parameters present, since they are molecularly determined), using a 100-fold range of time constants for a unique and somewhat physiologically homogeneous population of neurons seems biologically unrealistic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The few intracellular studies addressing this question have shown that the membrane potential of IC neurons can phase-lock to the modulation envelope in response to SAM tones (Casseday et al 1994;Leary et al 2008) and that the amplitude of this response decreases with higher modulation frequencies (Tan and Borst 2007). In addition, several models have been made for bandpass rate tuning to AM stimuli, but essential features of these models, such as coincidence detection (Borst et al 2004;Guérin et al 2006;Hewitt and Meddis 1994;Langner 1981), the presence of feedback (Friedel et al 2007), or rate-tuned inhibition (Dicke et al 2007;Carney 2004, 2007), have not yet been tested.…”
Section: Introductionmentioning
confidence: 99%
“…Hewitt and Meddis (1994) simulated the transformation of a temporal code for amplitude modulation in cochlear-nucleus sustained-chopper cells into a rate code of amplitude modulation through inferior-colliculus coincidence-detector cells. Ongoing experiments in our lab try to localize the neural substrate for the transformation of roughness into a rate code.…”
Section: Discussionmentioning
confidence: 99%